Subwavelength-grating coupled-cavity resonance VCSELs with ultra-narrow linewidth - Li-shan Fu; Ning Cui; Feng Zhang; Ji-sheng Wang; Ao Qiu; Bao-lu Guan; Ai-Qun Liu (APL Photonics)
Vertical-cavity surface-emitting lasers (VCSELs) characterized by compactness, high stability, and narrow linewidths are of significant interest for miniature atomic sensing applications. However, to date, experimental implementations of ultra-narrow linewidth VCSELs below 5 MHz are lacking. Here, we present a dual-cavity coupled VCSEL that employs a guided-mode resonance grating (GMRG) structure to achieve extremely narrow linewidth outputs. Through comprehensive simulation and optimization of the GMRG parameters, a coupled-cavity subwavelength-grating resonance VCSEL (CCG-VCSEL) design was developed, resulting in a cold-cavity linewidth output of 5 pm. It has been experimentally demonstrated that the CCG-VCSEL achieves an ultra-narrow linewidth of 2.74 MHz, which is one-fiftieth of the linewidth of a traditional VCSEL (100 MHz). In addition, it is comparable to DBR/DFB semiconductor lasers, which are less integrated than it. Furthermore, the CCG-VCSEL also exhibits a low threshold current of 0.37 mA and an output power of 2.5 mW. At ambient temperature, the optical polarization suppression ratio (OPSR) achieves 40 dB, signifying exceptional single-polarization performance. Notably, the CCG-VCSEL maintains stable single-mode operation even at elevated temperatures of 80 °C. This device provides a mighty solution for the technique of next-generation miniaturized integrated VCSELs, offering a reliable narrow-linewidth light source for high-precision applications, such as chip-scale atomic clocks.